2023
DOI: 10.3390/cells12091239
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Motility Annotated Genes: Are They Associated with Impaired Fecundity?

Abstract: Sperm motility is a prerequisite for achieving pregnancy, and alterations in sperm motility, along with sperm count and morphology, are commonly observed in subfertile men. The aim of the study was to determine whether the expression level of genes annotated with the Gene Ontology (GO) term ‘sperm motility’ differed in sperm collected from healthy men and men diagnosed with oligoasthenozoospermia. Reverse transcription quantitative real-time PCR (RT-qPCR), quantitative mass spectrometry (LC-MS/MS), and enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Additionally, the involvement of miRNAs in male infertility development is widely accepted, with observed alterations in miRNA expression levels in human sperm, seminal plasma, and testicular tissue of men with various patterns of non-obstructive azoospermia [ 8 ]. In recent studies, a correlation has been observed between the differential expression of miRNAs and/or their target mRNAs levels, and basic semen parameters, notably sperm motility [ 9 , 10 ]. This correlation suggests that miRNAs and/or their target mRNAs can potentially serve as diagnostic, prognostic, and even therapeutic biomarkers for male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the involvement of miRNAs in male infertility development is widely accepted, with observed alterations in miRNA expression levels in human sperm, seminal plasma, and testicular tissue of men with various patterns of non-obstructive azoospermia [ 8 ]. In recent studies, a correlation has been observed between the differential expression of miRNAs and/or their target mRNAs levels, and basic semen parameters, notably sperm motility [ 9 , 10 ]. This correlation suggests that miRNAs and/or their target mRNAs can potentially serve as diagnostic, prognostic, and even therapeutic biomarkers for male infertility.…”
Section: Introductionmentioning
confidence: 99%